BIOFLOCCULANT PRODUCTION FROM PLANTAIN (Musa paradisiaca) PEELS USING Aspergillus niger ISOLATED FROM WATER SEDIMENT - ZAINAB JUMAI, KASSIM; ISAH LEGBO, MOHAMMED; JIBRIN NDEJIKO, MOHAMMED; RAHMAT MUMMY, ISAH (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Bioflocculants have gain substantial consideration as potential substitute to chemical flocculating agents because they are biodegradable and produce no toxic effect. This study evaluates Musa paradisiaca peels as nutrient source for bioflocculant production. plantain peels were collected from Minna, Niger State, Nigeria. The hemmer milled peels were pulverized to fine powder, sieved and refluxed with NaOH in Erlenmeyer flask containing 1L distilled water and autoclaved at 121°C. The A. niger isolated from the water sediment of Bosso dam were grown in plantain peel broth supplemented with different nitrogen and carbon sources to produce the bioflocculant. A suspension of Kaolin (4 g/L) was used as model wastewater for estimating flocculating efficiency of the produced crude bioflocculant. The four (4) fungi namely Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus and Trichophyton spp isolated from the water sediment yielded bioflocculation efficiency of 80.1% ± 1.9, 73.7 ± 5.0%, 72.8 ± 2.1, and 66% ±1.8, prompting the used of A. niger for subsequent investigations. Yeast extract (95%) and peptone (91%) were the most preferred nitrogen source while glucose, maltose, fructose and sucrose all show remarkable bioflocculant production when used as supplementary carbon sources (83 to 86.9% flocculation efficiency). The utilization of plantain peels to produces bioflocculant can resourcefully lower the cost of bioflocculant production and offers an alternative strategy of handling environmental pollution by the Plantain peels as well maximizing the use of biomolecules in the peels.